PERBANDINGAN NILAI DAYA DUKUNG PONDASI BORE PILE MENGGUNAKAN HASIL UJI SONDIR DAN SPT PADA PROYEK PEMBANGUNAN JEMBATAN ARANAWAY KABUPATEN BANJAR - Gazali, Akhmad; Fathurrahman, Fathurrahma; Ariswandy, Muhammad Rego (Universitas Lambung Mangkurat, 2023)
Soil bearing capacity is very important in building infrastructure that affects the pavement layer above it, as it is the subgrade that will support the loading. Therefore, soil is the most important aspect as the main support in civil engineering building structures. The purpose of this study is to determine the comparison of Bore Pile bearing capacity analysis according to soil investigation data in the form of Sondir (CPT) and Machine Drill (SPT) with two methods, namely the Mayerhoff and Aoki & De Alencer methods in the construction of the Aranaway Bridge. After calculating with Aoki & De Alencer, the ultimate carrying capacity is 137.47 tons (CPT 1) and 113.83 tons (CPT 2). While the calculation with Mayerhoff with the results of the ultimate bearing capacity of 258.12 tons (SPT 1) and 200.04 tons (SPT 2). According to the calculation, it is also obtained a comparison of the bore pile permit bearing capacity for Aoki & De Alencer of 68.74 tons and 57.42 tons on Sondir data, while for the Mayerhoff method of 86.04 tons and 66.68 tons on SPT data. So it is concluded that the value of the allowable carrying capacity of the two methods, the difference is not significant.